Model-based pore-pressure prediction in shales: An example from the Gulf of Mexico, North America - Han, T.; Pervukhina, Marina; Clennell, M.; Dewhurst, D. (Society of Exploration Geophysics, 2017)
Accurate pore-pressure interpretation and prediction play important roles in understanding the sedimentary history of a basin and in reducing drilling hazards during hydrocarbon exploitation. Unlike typical reservoir rocks, in which pore pressures can be directly measured, pore pressures in shale must be inferred via their state of compaction.We have used the shale acoustic properties to accomplish this. Shale P- and S-wave velocities were first calculated using an anisotropic differential effective medium model. This model was built using elastic properties of wet clay mineralogy, and the total porosity of the shale was obtained from basic open-hole well-log measurements. These simulated shale velocities were systematically higher than sonic velocities observed on a test data set from a Gulf of Mexico well, penetrating a 1200 m vertical section of overpressured shale. The difference between the modeled velocities and the sonic measurements was then evaluated to estimate the abnormal pore pressure based on an exponential relationship between the pore pressure and the ratio of measured to modeled velocity. Using a reasonable exponent, the predicted pore pressure was shown to be in good agreement with direct pore-pressure measurements either made in adjacent sand layers that are thought to be in pressure equilibrium with the shales or inferred from drilling mud weights.